Entrepreneurial, renewal capitals and financial performance. Evidences from an international research project - DeMartini, Paola; Cesaroni, Francesca Maria; Del Baldo, Mara; Paoloni, Paola (Piccola Impresa / Small Business, 2017)
In most studies IC (Intellectual Capital) has been seen to consist of three elements: human capital, structural capital and relational capital. However, emerging studies suggest that that three other elements could also be included in IC visualizing and mapping: renewal capital (RC), trust capital (TC), and entrepreneurial capital (EC). The purpose of this paper is to show preliminary results from the Italian research unit of an international project on IC and value creation. We focused on EC and RC, in order to verify if they affect firm performances. Descriptive analysis techniques were applied. We utilized multi-item scales as the key constructs to operationalise entrepreneurial capital and renewal capital. Statistical analysis revealed a significant positive relationship between EBITDA and EC. Moreover, statistical data also confirm the existence of a positive influence of RC and EC levels on ROI and a positive relationship between ROA and RC